Water-soluble polyelectrolyte complex nanocoating for flame retardant nylon-cotton fabric. (December 2015) - Leistner, Marcus; Haile, Merid; Rohmer, Sarah; Abu-Odeh, Anas; Grunlan, Jaime C.
Abstract: Blends of cotton with synthetic fibers are widely used for various military and industrial applications. Nylon-cotton (NYCO) blends offer high durability and strength from nylon and the softness of cotton, but both fiber types are highly flammable. Previously reported flame retardant coatings for cotton fabric, comprised of a complex of polyethylenimine and a polyphosphate, are not able to protect NYCO textiles, so a new generation of water-soluble polyelectrolyte complex coating is needed. The basis of this new treatment is an aqueous complex of polyethylenimine and ammonium polyphosphate that forms melamine polyphosphate in-situ during exposure to a melamine-containing solution. NYCO fabric was rendered self-extinguishing in a vertical flame test and pyrolysis combustion flow calorimetry showed a 28% reduction in total heat release, and a 65% reduction of cotton's peak heat release, with less than 20 wt% coating. The effectiveness of this halogen-free, flame retardant coating is due to condensed phase activity that includes cooling effects and charring. The ease of this coating procedure and the use of more environmentally benign chemicals deposited from aqueous solutions make this an industrially feasible alternative to current treatments.